2017
DOI: 10.3389/fmolb.2017.00083
|View full text |Cite
|
Sign up to set email alerts
|

Protein Translocation into the Intermembrane Space and Matrix of Mitochondria: Mechanisms and Driving Forces

Abstract: Mitochondria contain two aqueous subcompartments, the matrix and the intermembrane space (IMS). The matrix is enclosed by both the inner and outer mitochondrial membranes, whilst the IMS is sandwiched between the two. Proteins of the matrix are synthesized in the cytosol as preproteins, which contain amino-terminal matrix targeting sequences that mediate their translocation through translocases embedded in the outer and inner membrane. For these proteins, the translocation reaction is driven by the import moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 102 publications
2
75
0
2
Order By: Relevance
“…The IMS environment was characterized using a "bipartite presequence" from two IMS proteins: OPA1 (MTS-OPA1) and apoptosis inducing factor AIFM1 (MTS-AIFM1). A "bipartite presequence" is a feature of a subset of IMS proteins that contain an MTS, followed by a cleavable stop-transfer sequence, which, upon cleavage, results in "soluble" IMS protein (Backes and Herrmann, 2017). Our IMS-BirA* baits identified 120 proximity interactors, of which 112 (93%) were annotated as mitochondrial proteins by either Mitocarta 2.0 or Gene Ontology Cellular Component (GOCC) (Supplementary Fig.…”
Section: Definition Of the Mitochondrial Matrix And Ims Bioid Environmentioning
confidence: 99%
“…The IMS environment was characterized using a "bipartite presequence" from two IMS proteins: OPA1 (MTS-OPA1) and apoptosis inducing factor AIFM1 (MTS-AIFM1). A "bipartite presequence" is a feature of a subset of IMS proteins that contain an MTS, followed by a cleavable stop-transfer sequence, which, upon cleavage, results in "soluble" IMS protein (Backes and Herrmann, 2017). Our IMS-BirA* baits identified 120 proximity interactors, of which 112 (93%) were annotated as mitochondrial proteins by either Mitocarta 2.0 or Gene Ontology Cellular Component (GOCC) (Supplementary Fig.…”
Section: Definition Of the Mitochondrial Matrix And Ims Bioid Environmentioning
confidence: 99%
“…CHCHD4 provides an import and oxidoreductase-mediated protein folding function along with the sulfhydryl oxidase GFER (ALR/Erv1) as a key part of the disulphide relay system (DRS) within the mitochondrial IMS [5][6][7]. As such, CHCHD4 controls the import of a number of mitochondrial proteins that contain a twin-CX 9 C or twin-CX 3 C motif [8][9][10].…”
mentioning
confidence: 99%
“…Based on these data, it was suggested that ferredoxin transport occurs by means of a Brownian ratchet mechanism in which FusC acts as a periplasmic anchor to facilitate translocation of ferredoxin across the OM via the lumen of FusA 12,15 . Similar mechanisms have been postulated to account for mitochondrial protein uptake, whereby cytoplasmically synthesised proteins are translocated via the TOM and TIM23 complexes 16,17 . As such, this would represent a hitherto unexpected evolutionary link between mitochondrial and plastid protein import and bacterial protein import via the Fus and other postulated protein uptake systems.…”
Section: Introductionmentioning
confidence: 71%